Ampelomyces quisqualis Ces. â€“ a mycoparasite of Euphorbia hirta powdery mildew in Himachal Pradesh, India - Gautam, A. K.; Avasthi, Shubhi (Journal of Phytopathology and Disease Management, 2016)
Mycoparasitism is defined as the association of two fungi where one acts as parasite over the other. In October 2015, a powdery mildew infection was observed on Euphorbia hirta during the routine mycological survey in district Mandi the central region of Himachal Pradesh, India. During the course of microscopic examinations infection was found mixed with another unknown fungus. Upon morphological and microscopic examinations of infection on leaves, Podosphaera euphorbiae-hirtaeÂ was identified as powdery mildew fungus mixed with a mycoparasite Ampelomyces quisqualis. To the best of our knowledge, this is the first report of mycoparasitism of Ampelomyces quisquali on powdery mildew of Euphorbia hirta in India.